Optimizing the Role and Function of Managers in Nurse Performance Assessment or Ongoing Professional Practice Evaluation - Wildan Wildan; Andi Amalia Wilda; Sarvita Dewi (Indonesian Journal of Global Health Research, 2025)
The success of healthcare organizations depends heavily on the quality of human resources, particularly nurses, who play a critical role in the organization's growth and sustainability. Performance evaluation, such as Ongoing Professional Practice Evaluation (OPPE), is essential to assess nurses' contributions, productivity, and competencies. Objective: This study aims to optimize the role and function of managers in nurse performance evaluation through the OPPE approach.Methods: The study employed a case study method with a pilot study approach involving 21 nurses at RSAB Harapan Kita. Data collection was conducted through interviews, observations, and questionnaires. Problems were analyzed using the Ishikawa diagram, followed by problem prioritization, action planning, and implementation based on the POSAC method (Planning, Organizing, Staffing, Actuating, Controlling). Results : The analysis revealed that performance evaluation was not optimal, with outdated guidelines, the absence of standard operating procedures (SOPs), and irrelevant assessment tools. Current OPPE evaluations showed behavior scores at 48.5%, clinical performance at 93.5%, and professional development at 55.5%. Interventions included developing updated guidelines, SOPs, and relevant assessment tools. Conclusion: Optimizing managers' roles through updated guidelines, SOP development, and improved assessment tools significantly enhanced the effectiveness of performance evaluations. The implementation of tiered supervision and periodic evaluations is expected to improve nursing service quality and support the sustainable achievement of organizational vision and mission.